Patients' subjective assessment as a decisive predictor of malignancy in pelvic masses: results of a multicentric, prospective pelvic mass study. (3rd July 2022) - Koch, Elisa; Torsten, Uwe; Mecke, Herbert; Richter, Rolf; Hellmeyer, Lars; Nohe, Gerhard; Müller, Bodo; Boeneß-Zaloum, Janine; Ames, Kerstin; Chen, Frank; Beteta, Carmen; Hasenbein, Kati; et al.
Abstract: Objective: The prognosis for ovarian cancer patients remains poor. A key to maximizing survival rates is early detection and treatment. This requires an accurate prediction of malignancy. Our study seeks to improve the accuracy of prediction by focusing on early subjective assessment of malignancy. We therefore investigated the assessment of patients themselves in comparison to the assessment of physicians. Methods: One thousand three hundred and thirty patients participated in a prospective and multicenter study in six hospitals in Berlin. Using univariate analysis and multivariate logistic regression models, we measured the accuracy of the early subjective assessment in comparison to the final histological outcome. Moreover, we investigated factors related to the assessment of patients and physicians. Results: The patients' assessment of malignancy is remarkably accurate. With a positive predictive value of 58%, the majority of patients correctly assessed a pelvic mass as malignant. With more information available, physicians achieved only a slightly more accurate prediction of 63%. Conclusions: For the first time, our study considered subjective factors in the diagnostic process of pelvic masses. This paper demonstrates that the patients' personal assessment should be taken seriously as it can provide a significant contribution to earlier diagnosis and thus improved therapy and overall prognosis.